Analisis Gangguan Fonologi Pada Penderita Cadel dalam Pelafalan Konsonan R : (Studi Kasus Fonologi) - Sri Susanti; Hendra Setiawan (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research analyzes phonological disorder patterns in the pronunciation of the /r/ consonant among university students with rhotacism. The study focuses on Wardah Zahra, a 20-year-old student who has experienced difficulty pronouncing the /r/ consonant since childhood. Using a descriptive qualitative approach with interview techniques and pronunciation analysis, the research reveals consistent substitution patterns where the /r/ consonant is pronounced as /l/ and /w/, particularly in medial and final word positions. Phonetic and phonemic analysis uncovers pronunciation variations that are consistent across initial, medial, and final word positions. Psychological factors such as self-confidence also influence the development of pronunciation disorders. Research findings indicate that adult rhotacism patients develop adaptive communication strategies and exhibit relatively stable pronunciation patterns. Although there are variations in disorder severity, consistency is found in phonological substitution patterns. This research provides an in-depth understanding of phonological disorder characteristics in adult rhotacism patients and can serve as a foundation for developing more effective interventions.